Prevalence and factors associated with microvascular and macrovascular diabetes complications in adult Ugandans: A systematic review and meta-analysis - Davis Kibirige; Ronald Olum; William Turyamureeba; Bethan Morgan; Andrew Peter Kyazze; Yakobo Nsubuga; Jerom Okot; William Lumu; Felix Bongomin (PLoS ONE, 2026)
Introduction The rising prevalence of diabetes in Uganda has led to a disproportionate increase in the burden of diabetes complications. We conducted a systematic review and meta-analysis to document the prevalence and factors associated with five chronic diabetes complications in adult Ugandans with diabetes. Methods We searched Medline, EMBASE, CINAHL, Cochrane Library, and Africa Journal Online databases from 25 th May 2024–29 th May 2024. We included studies reporting information on the prevalence and factors associated with the five chronic diabetes complications. We conducted a random-effect meta-analysis to determine the pooled prevalence of each diabetes complication. Using narrative synthesis, we described the factors significantly associated with each diabetes complication. Results A total of twenty studies reporting information on 11,400 participants were considered. The pooled mean (standard deviation) age of the participants was 54.8 (3.6) years. For the microvascular diabetes complications, the pooled prevalence of diabetic neuropathy, retinopathy, and nephropathy was 56.8% (95% CI 44.9–68.7, I 2 = 98.56%, p < 0.001), 19.5% (95% CI 3.9–35.2, I 2 = 99.60%, p < 0.001), and 17.7% (95% CI 7.3–28.0, I 2 = 99.36%, p < 0.001), respectively. For the macrovascular diabetes complications, the pooled prevalence of peripheral arterial disease and diabetic foot disease was 32.2% (95% CI 15.8–48.7, I 2 = 97.67%, p < 0.001) and 5.5% (95% CI 1.7–9.2, I 2 = 90.22%, p < 0.001), respectively. Hypertension comorbidity, physical inactivity, family history of diabetes, body mass index ≤30 kg/m 2 , and pregnancy were associated with diabetic nephropathy in three studies. In two studies, a history of a foot ulcer and age > 60 years were associated with diabetic neuropathy, while female sex, hypertension comorbidity, and use of glibenclamide were associated with peripheral arterial disease. Conclusions This study demonstrates a high prevalence of chronic diabetes complications in adult Ugandans with diabetes. Timely screening and optimal management of chronic diabetes complications should be encouraged in Uganda.